THE COMPETITION BETWEEN MACAQUES AND CAO VIT GIBBON IN TRUNG KHANH SPECIES & HABITAT CONSERVATION AREA, CAO BANG PROVINCE - Dac Manh, Nguyen; Van Dung, Tran; Tiến Thịnh, Vu (Journal of Forestry Science and Technology, 2020)
In the study, we surveyed the habitat characteristics of the Rhesus macaque (Macaca mulatta), Assamese macaque (Macaca assamensis) and Stump-tailed macaque (Macaca arctoides), and Cao vit gibbon (Nomascus nasutus), and their diet in Trung Khanh Species & Habitat Conservation Area from October to December 2018. Based on the comparison of food components (species and the parts of tree), and nine ecological niche factors (elevation, slope, the location of slope, aspect, the distance to water resource, vegetation type, tree density, distance to farm, distance to residential area), we assessed the competition levels on food and living space between each macaque and Cao vit gibbon. The results of the study showed that the competition on food between Rhesus macaque and Cao vit gibbon is very high while between Assam macaque, Stump-tailed macaque, and Cao vit gibbon is high. Three macaques and Cao vit gibbon compete for living space, in which Assam macaque is the most competitive species. Distance to a residential area, distance to farms, aspect, elevation, slope, and distance to water sources are the environmental factors in which the Cao vit gibbon and macaque are more competitive in fall-winter season. Finally, we have proposed the solutions to manage the macaque population and their habitat to decrease the competition between macaques species and gibbon in Trung Khanh Species & Habitat Conservation Area.